2020
DOI: 10.15517/aie.v20i2.41669
|View full text |Cite
|
Sign up to set email alerts
|

Consciousness-raising tasks for the mediation of text structure, cohesion, and coherence in essay writing

Abstract: Several studies have demonstrated the positive impact of Consciousness-Raising tasks (CRTs) on the teaching of grammar, especially in foreign or second language learning. However, few studies have examined their effectiveness for the development of writing skills. With this in mind, the goal of this project is to explore the impact of CRTs on three aspects of writing in expository essays: text structure, cohesion, and coherence. To accomplish this goal, the study followed a mixed-method approach with a compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…For example, Khojasteh et al (2021) showed that students who have an orientation to flippedbased mediation improved students mastery of writing relevant content, idea organization, vocabulary use, language use, and mechanics. Likewise, Vargas et al (2020) investigation revealed a similar conclusion that mediation of text structure, cohesion, and coherence through conscious-raising tasks of essay writing improved experiential group performance. Poehner and Infante (2016) also revealed that the mediator guidance and support provided to Second Language students helped them acquire the tense aspects system.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…For example, Khojasteh et al (2021) showed that students who have an orientation to flippedbased mediation improved students mastery of writing relevant content, idea organization, vocabulary use, language use, and mechanics. Likewise, Vargas et al (2020) investigation revealed a similar conclusion that mediation of text structure, cohesion, and coherence through conscious-raising tasks of essay writing improved experiential group performance. Poehner and Infante (2016) also revealed that the mediator guidance and support provided to Second Language students helped them acquire the tense aspects system.…”
Section: Discussionmentioning
confidence: 63%
“…The investigations done by (Khojasteh et al, 2021;Poehner & Infante, 2016;Ruzek et al, 2016;Situmorang, 2022;Tum, 2020;and Vargas et al, 2020;) examined the effects of interventions on efficacious belief; this study opens new insights on improving belief sources based on rigorous and demanding classroom mediational moves in the ways of tackling curious self-efficacious difficulties students usually face in developing paragraph and essay writing skills.…”
Section: Discussionmentioning
confidence: 99%
“…Menurut Amaechi & Edwin (2019), kohesi perulangan hendaklah digunakan secara meluas dalam penulisan karangan bagi meningkatkan kualiti penulisan yang dihasilkan oleh murid. Hal ini demikian kerana penggunaannya dalam penulisan karangan berkesan menautkan kata, frasa dan ayat dalam mewujudkan kesinambungan agar mesej penulisan dapat disampaikan dengan jelas kepada pembaca (Klarer, 1999;Gutkind, 2012;Vargas et al, 2020).…”
Section: Pengenalanunclassified